2023
DOI: 10.3390/bioengineering10091059
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of Head–Neck Kinematics in Rear-End Impact Conditions with Headrest

Yuan Wang,
Hanhui Jiang,
Ee Chon Teo
et al.

Abstract: A detailed three-dimensional (3D) head–neck (C0–C7) finite element (FE) model was developed and used to dictate the motions of each cervical spinal segment under static physiological loadings of flexion and extension with a magnitude of 1.0 Nm and rear-end impacts. In this dynamic study, a rear-end impact pulse was applied to C7 to create accelerations of 4.5 G and 8.5 G. The predicted segmental motions and displacements of the head were in agreement with published results under physiological loads of 1.0 Nm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The ENM-2D’s efficiency makes it ideal for optimization processes requiring a high number of simulations. Therefore, this model enables more efficient computational analysis in comparison to using 3D finite element models, such as for the seat design position and angle of the headrest conducted by Wang et al [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ENM-2D’s efficiency makes it ideal for optimization processes requiring a high number of simulations. Therefore, this model enables more efficient computational analysis in comparison to using 3D finite element models, such as for the seat design position and angle of the headrest conducted by Wang et al [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…During exposure to an MVC, the cervical spine is subjected to complex inertial loading where bending, shear, and compression loads act on the column. During the skull translation phase, many authors have described an S-Curve (first-order buckled mode) of the cervical lordosis [29][30][31][32][33]. Similarly, Matsunaga et al [34] described altered static cervical curvatures, including S-curves and retrolistheses, as buckled modes or shapes.…”
Section: Altered Sagittal Cervical Geometry As a Buckling Type Alignmentmentioning
confidence: 99%
“…In MVC's acceleration/deceleration events, during the skull translation phase, many authors have described an S-Curve (first-order buckled mode) of the cervical lordosis [29][30][31][32][33]. Furthermore, altered geometry of the static cervical curvatures of patients has been previously described as buckled modes/shapes [34], but to our knowledge no study has shown that MVC's cause or contribute to altered geometry of the cervical curve post-crash.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous investigation reports can be found in the literature that have attempted to characterize the cervical spine biomechanical response. Many of these investigations have tested animals [5], human volunteers [6], human cadavers [7], crash-test dummies [8], articulated artificial necks [9], and computational models [10][11][12].…”
Section: Introductionmentioning
confidence: 99%